Directive Speech Acts on the Statement of Prohibition of Homecoming for Lebaran 2021: A Critical Pragmatic Study - Uctuvia, Vina; Nurhayati, Nurhayati (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
Homecoming or mudik is a massive mobility culture of inter-city and inter-provincial residents within a certain period of time carried out by Muslims in Indonesia. Therefore, in an effort to control the spread of the Covid-19 virus in the period leading up to Eid al-Fitr, the government made an effort to ban homecoming in 2021. This statement was first conveyed by the President of the Republic of Indonesia, Joko Widodo, which was conveyed through the Presidential Secretariat's YouTube channel. The purpose of this study is to explore the types and functions of directive speech acts through a critical pragmatic approach. The method of this research is descriptive qualitative which uses listening and note-taking techniques. The data that has been collected is then analyzed using a critical pragmatic approach. The results of this study indicate that the directive speech acts in the prohibition of homecoming are conveyed there are three types of speech acts that are found in the speech produced by President Joko Widodo, Chairman of the Covid-19 Task Force Doni Monardo, Deputy Secretary General of PBNU Andi Najmi Fuadi, and General Secretary Muhammadiyah Abdul Mu'ti, namely; 1) The directive speech act appeals, 2) The directive speech act prohibits, and 3) The directive speech act commands. Of the three types of speech acts found, there are two types of clauses used to perform directive speech acts, namely; 1) Declarative clauses and 2) Imperative clauses. From the statements made by the President, the Covid-19 Task Force, and several religious figures, there is a good synergy so that the statement has the same purpose and function.